BIBLIOMETRIC REVIEW ON THE APPLICATION OF HOLOGRAMS IN IMMERSIVE ENVIRONMENTS IN THE CONTEXT OF UNIVERSITY TEACHING, 2013-2023 - FLORES-CÁCERES, RICHARD (2024)
HIGHER EDUCATION INSTITUTIONS ARE MAKING USE OF AUGMENTED REALITY AND VIRTUAL REALITY TO GENERATE IMMERSIVE ENVIRONMENTS AND IMPROVE STUDENT UNDERSTANDING. HOWEVER, OTHER TECHNOLOGIES, SUCH AS HOLOGRAMS, ALLOW FOR IMMERSION IN MORE REALISTIC SCENARIOS, HELPING TO REDUCE CERTAIN NEGATIVE EFFECTS ASSOCIATED WITH THE PROLONGED USE OF SO-CALLED MIXED REALITIES. THEREFORE, IT IS IMPORTANT TO USE BIBLIOMETRIC INDICATORS TO ANALYZE THE SCIENTIFIC PRODUCTION REGARDING THE APPLICATION OF HOLOGRAMS IN IMMERSIVE ENVIRONMENTS IN THE CONTEXT OF UNIVERSITY TEACHING, IN ORDER TO IDENTIFY GAPS AND TRENDING TOPICS THAT WILL CONTRIBUTE TO GUIDING FUTURE RESEARCH. THE STUDY FOLLOWED A QUANTITATIVE, DESCRIPTIVE APPROACH TO ANALYZE STUDIES EXTRACTED FROM THE SCOPUS DATABASE. THE RESULTS OBTAINED SHOW A GROWING TREND IN SCIENTIFIC PRODUCTION BETWEEN THE YEARS 2020 AND 2023, WITH 73.81% OF REVIEWED PUBLICATIONS BEING CONCENTRATED IN THAT PERIOD; THIS IS SIGNIFICANTLY HIGHER THAN THAT WHICH HAD BEEN PRODUCED IN PREVIOUS YEARS. FURTHERMORE, THE TRENDING TOPICS IDENTIFIED INCLUDED INTEGRATING HOLOGRAMS IN MIXED REALITY FOR IMMERSIVE LEARNING AND APPLYING HOLOGRAMS FOR SPATIAL UNDERSTANDING IN ENGINEERING. THUS, IT CAN BE CONCLUDED THAT THE APPLICATION OF HOLOGRAMS IN CERTAIN SPECIALTIES OF UNIVERSITY EDUCATION REMAINS LIMITED, INDICATING THAT THERE IS A GAP IN THEMATIC AREAS THAT MUST BE COVERED AND ADDRESSED IN FUTURE STUDIES; FOR EXAMPLE, THE APPLICATION OF HOLOGRAMS IN SOCIAL SCIENCES AND HUMANITIES SUBJECTS, THE INTEGRATION OF HOLOGRAPHIC TECHNOLOGY INTO THE CURRICULAR PLAN IN MATHEMATICS AND SCIENCE SUBJECTS AND THE USE OF DIGITAL HOLOGRAPHY IN MEDICAL EDUCATION. © 2024 SOCIETY FOR RESEARCH AND KNOWLEDGE MANAGEMENT. ALL RIGHTS RESERVED.